1998
DOI: 10.2165/00003088-199834050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Hydroxyurea

Abstract: Hydroxyurea is used in the treatment of various forms of cancer, sickle-cell anaemia and HIV infection. Oral absorption of the drug is virtually complete, the volume of distribution is equivalent to total body water and elimination is through both renal and nonrenal mechanisms. Nonrenal elimination of hydroxyurea is characterised by Michaelis-Menten kinetics. Further studies are necessary to clarify several aspects of the pharmacokinetics and pharmacodynamics of hydroxyurea: the effect of age and disease state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 48 publications
3
110
1
3
Order By: Relevance
“…This level of substrate was assumed to be biologically feasible given the high millimolar concentrations of hydroxyurea that can established [32]. Furthermore, these conditions were chosen to optimize evaluation of the reaction given the concentration of GSH (100 μM) required for the assay.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This level of substrate was assumed to be biologically feasible given the high millimolar concentrations of hydroxyurea that can established [32]. Furthermore, these conditions were chosen to optimize evaluation of the reaction given the concentration of GSH (100 μM) required for the assay.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
“…Although in vivo concentrations of NH 2 OH and NOHA are not well established, the pharmokinetics of hydroxyurea are better understood. At a standard 20 mg/kg dose of hydroxyurea, maximum serum levels can exceed 100 mM [32]. Although such levels are expected only from exogenous sources, the demonstrated ability to accumulate hydroxylamines suggests the possibility that this class of compound may function as endogenous precursors of HNO.…”
Section: Introductionmentioning
confidence: 99%
“…HU is rapidly eliminated from both humans (t 1/2~4 h) and nude mice (t 1/2~1 1 min). [26][27][28] Mayhew et al 29 treated mice with 500 mg/kg/day HU for 10 weeks without signs of gross toxicity or significant differences in body weight, although hematopoietic toxicity occurred past 2 weeks. In preliminary studies, we treated nude mice for 5 consecutive days with 500, 1000 or 1500 mg/kg HU without any observed adverse behavior effects or weight loss during treatment or 100 days following treatment (data not shown).…”
Section: Sensitivity Of Sw620 Tumors To Gcv and Hu In A Murine Xenogrmentioning
confidence: 99%
“…HU already has a proven history of clinical application and has been shown to be a good biochemical modulator in combination with other chemotherapeutic agents. 26 In addition, HU treatment could be used with a variety of expression vectors, tissue specific vectors, or more active HSVtk mutants. This strategy also has the advantage of not requiring additional transgene expression such as previously reported connexin overexpression 38,39 or addition of a second suicide gene.…”
Section: Gene Therapymentioning
confidence: 99%
“…HU and thiosemicarbazones are known to inhibit the cell cycle in the G1/S phase, mainly inactivating ribonucleotide reductase, an enzyme that mediates the conversion of ribonucleotides to deoxyribonucleotides (13). Recently, we demonstrated that TSC and analog compounds, 4-thiazolidinones (4-TZD), decreased in vitro infection and eliminated intracellular T. gondii (14).…”
Section: Introductionmentioning
confidence: 99%